THE TRANSLATION OF IDIOMATIC EXPRESSION IN BLOODLINE INTO â€œGARIS DARAHâ€ - Putu Astari Hendrawati; I Wayan Budiarta (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2017)
Abstract The aims of this thesis are to figure out the techniques and process of translation of English idiom into Indonesian Language. The data were taken from a Novel by Sidney Sheldon entitled â€œBloodlineâ€ and its translation Garis Darah. The collected data was analyzed by using qualitative and quantitative methods. The data of this study were collected by identifying and classifying the data based on the idioms and translation procedures by using Hocket (1958). Another theory is from Vinay & Dalbernetâ€™s (1995) and also supported by a theory proposed by Catford (1978). Through classification based on the theory there are three types of idioms, they are English phrasal compound that is divided into three parts such as the close form, the hyphenated form and the open form; figure of speech that is divided into four parts such as simile, hyperbole, metaphor, and personification; and slang. All types of idioms are applied in this thesis and it is found there are 289 data. The close form is 3, the hyphenated form is 16, the open form is 11, simile with 42 data, metaphor and personification are 26, hyperbole is 33, and slang is 132 data. On the other hand, there are seven techniques of translation according to the theory, they are borrowing, calque, literal, transposition, modulation, adaptation, and equivalence. All techniques are applied in this thesis. The most dominant translation technique that is applied in this thesis is adaptation with the percentage of 33,5% (97 data), the second is literal with 33,2% (96 data), modulation and equivalence has same percentage as 10,3% (30 data), transposition is 9,3% (27 data), borrowing with 2,76% (8 data), and the last is calque with 0,34% (1 data). Keywords: techniques of translation, idiomatic expression, languages